1109. Rise and Fall of COVID-19 Therapies Throughout Different Waves of the Pandemic: Results of a Nationwide Survey. (15th December 2022) - Mena Lora, Alfredo J; Herald, Fischer; Lindsey, Brenna; Borgetti, Scott; Chaisson, Lelia H; Burgos, Rodrigo M; Bleasdale, Susan C
Abstract: Background: The COVID-19 pandemic has caused a major public health crisis and is now a leading cause of death. At the start of the COVID-19 pandemic, treatment was limited to supportive care and off-label use of a variety of agents as we awaited the results of randomized controlled trials (RCTs). Our understanding of the disease has evolved and multiple evidence-based (EBM) treatment strategies supported by RCTs are now approved for use. Interpreting emerging data while responding to the pandemic can been challenging. We seek to understand the use of common medications during the COVID-19 pandemic. Methods: A survey was developed and disseminated through Infectious Diseases Society of America (IDSA) IDea network, IDSA Antimicrobial Stewardship Centers for Excellence and the Society for Healthcare Epidemiology messaging boards. Data collected included city, therapeutic options including convalescent plasma (CP), hydroxychloroquine (HCQ), baricitinib and tocilizumab during each COVID-19 wave. Results: A total of 78 responses were collected, representing wide geographic reach in the US (Figure 1). Use of HCQ declined by 96% and use of CP declined by 85% (Figure 2). The decline in CP was gradual each wave despite RCTs showing lack of benefit. Tocilizumab was used in 71% and 76% of hospitals during the first wave, prior to RCT data supporting its use. Baricitinib was used in 42% of hospitals prior to RCT data supporting its use. There was a 90% increase in baricitinib use after RCT data emerged. Figure 1 Geographic distribution of hospitals represented in the survey Figure 2 Use of Hydroxychloroquine, Convalescent Plasma, Tocilizumab and Baricitinib Throughout Different COVID-19 Waves Conclusion: The use of therapies before proven benefit was common through the pandemic. Similarly, the use of therapies after benefit was in question continued. Hydroxychloroquine was widely used in the first wave and then halted by the majority of hospitals in subsequent COVID-19 surges. IL-6 and JAK-2 inhibitors were commonly used prior to evidence of benefit and were more widely adopted once evidence emerged. Convalescent plasma use was common despite lack of evidence and its use continued despite multiple negative RCTs. Overall, our survey shows a gap between evidence and practice. Communicating evidence-based treatment strategies is a vital priority for major professional societies. Translating evidence into practice remains challenging during public health emergencies like the COVID-19 pandemic. Disclosures: All Authors : No reported disclosures.